Determinants of Financial Statement Integrity - Hia, Hidayanti; Kusumawardhani, Indra (Journal of International Conference Proceedings, 2023)
Firms and financial statements are closely related. This study examine whether intellectual capital, managerial ownership, institutional ownership and firm size affect Â the integrity of financial statements. This study uses the consumer goods sector firms that have been listed on the Indonesia Stock Exchange (IDX) in 2017-2021. Purposive sampling is used as a method of selecting research samples and analyzed by multiple regression methods. The result show that intellectual capital, managerial ownership and firm size affect the integrity of financial statements. But institutional ownership does not affect the integrity of financial statements.